Growth Characteristics of Lizard Fish (Fam: Synodontidae) in the South China Sea - Ambak, Mohd Azmi; Mohammad Mohsin, Abu Khair; Mohd Said, Mohd Zaki (1986)
A study of growth characteristics of synodontids of Malaysia was carried out in waters within the Exclusive Economic Zone, South China Sea. Five age groups were identified for Saurida tumbil and four for S. undosquamis. Growth parameters of the von Bertalanffy equation for the two species are presented.